TINGKAT KESADARAN TERHADAP KESEHATAN TELINGA DAN PENDENGARAN DI MASYARAKAT CIANGSANA-NAGRAK - Melati, Tiara; Agustawan, Dwi; Nasution, Dina Putri; Riyadi, Vicky; Abdillah, Fauzan (Jurnal Pengabdian Masyarakat Trimedika, 2024)
This community service aims to measure the awareness regarding ear and hearing health of Ciangsana-Nagrak residents. It also aims to measure the frequency of ear or hearing problems in said population. Health promotion and ear health check-up were done simultaneously, where the residents were also asked to answer a questionnaire before and after they received a short education about various ear and hearing problems. Health education was done using standing banners and flip charts. All filled and submitted surveys were collected as raw data. Data analysis was done on raw data using descriptive analysis and paired t-test by Microsoft Excel 365 software. Health check-ups on ear health include examination, ear toilet, and treatment of ear ailments. Seven ear ailments found in this community service were impacted ear wax uni- and bilateral, chronic suppurative otitis media, vertigo, external cholesteatoma, tinnitus, and previously perforated bilateral tympanic membrane. The P value of the questionnaire before and after education was 0.007. Henceforth indicating the importance of ear health and hearing education and statistically significant in promoting public awareness of Ciangsana-Nagrak population.